Three-Dimensional Kinematics of the Human Metatarsophalangeal Joint during Level Walking - Raychoudhury, Sivangi; Hu, Dan; Ren, Lei (Frontiers in Bioengineering and Biotechnology, 2014)
The objective of this study is to investigate the three-dimensional (3D) kinematics of the functional rotation axis of the human metatarsophalangeal (MP) joint during level walking at different speeds. A 12 camera motion analysis system was used to capture the 3D motion of the foot segments and a six force plate array was employed to record the simultaneous ground reaction forces and moments. The 3D orientation and position of the functional axis (FA) of the MP joint were determined based on the relative motion data between the tarsometatarsi (hindfoot) and phalanges (forefoot) segments. From the results of a series of statistical analyses, it was found that the FA remains anterior to the anatomical axis (AA), defined as a line connecting the first and fifth metatarsal heads, with an average distance about 16% of the foot length across all walking speeds, and is also superior to the AA with an average distance about 2% of the foot length during normal and fast walking, whereas the FA shows a higher obliquity than the AA with an anteriorly more medial and superior orientation. This suggests that using the AA to represent the MP joint may result in overestimated MP joint moment and power and also underestimated muscle moment arms for MP extensor muscles. It was also found that walking speed has statistically significant effect on the position of the FA though the FA orientation remains unchanged with varying speed. The FA moves forwards and upwards toward a more anterior and more superior position with increased speed. This axis shift may help to increase the effective mechanical advantage of MP extensor muscles, maximize the locomotor efficiency, and also reduce the risk of injury. Those results may further our understanding of the contribution of the intrinsic foot structure to the propulsive function of the foot during locomotion at different speeds.